The Role of Collaborative Wiki and KWL Framework in Advancing Cognitive Development and Learning Motivation in Elementary Schools - Jamilatun, Jamilatun; Lupi , Andrayani; Ali, Furqon; Endra, Priawasana (Journal of Education Technology and Inovation, 2025)
The integration of technology in elementary education is vital to support students' cognitive development and motivation. Despite its potential, effective synergy between collaborative digital tools and reflective learning strategies remains underexplored in classroom practice. This study investigates the effects of integrating collaborative wikis and the Know–Want–Learn (KWL) framework on cognitive development and learning motivation among fifth-grade students in Jember, Indonesia. Using a quasi-experimental design with a mixed-method approach, the study involved 120 students assigned to experimental and control groups. Data were collected via pre- and post-tests, motivation questionnaires based on the ARCS model, classroom observations, and interviews. ANCOVA results revealed a significant increase in cognitive scores in the experimental group (F(1,117) = 28.59, p < 0.001), with motivational improvements noted across all four ARCS components. These findings demonstrate that the integration of wikis and KWL promotes reflective, collaborative, and engaging learning. The study contributes to the development of context-sensitive pedagogical models, particularly valuable for under-resourced primary education settings